2016
DOI: 10.1021/acs.nanolett.6b02061
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of Fermi Level Pinning at the Surface of Intrinsically n-Type InGaAs Nanowires

Abstract: Surface effects strongly dominate the intrinsic properties of semiconductor nanowires (NWs), an observation that is commonly attributed to the presence of surface states and their modification of the electronic band structure. Although the effects of the exposed, bare NW surface have been widely studied with respect to charge carrier transport and optical properties, the underlying electronic band structure, Fermi level pinning, and surface band bending profiles are not well explored. Here, we directly and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“…The increase in the surface states density leads to a shift of the Fermi level towards the neutrality level where it is pinned in both intrinsic and n-doped nanowires as soon as the surface states density exceeds 10 12  cm −2 . The latter is in agreement with the recent direct measurement of the Fermi level position at the surface of intrinsic InGaAs nanowires exposed to air 41 . What is more important, that Fig.…”
Section: Theoretical Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in the surface states density leads to a shift of the Fermi level towards the neutrality level where it is pinned in both intrinsic and n-doped nanowires as soon as the surface states density exceeds 10 12  cm −2 . The latter is in agreement with the recent direct measurement of the Fermi level position at the surface of intrinsic InGaAs nanowires exposed to air 41 . What is more important, that Fig.…”
Section: Theoretical Modelsupporting
confidence: 92%
“…In InAs nanowires with a wurtzite crystal structure the electron effective mass is larger, and the Fermi level pinning occurs at about 0.2 eV above the conduction band edge (ref. 41) opposite to 0.16 eV, as we considered. We do not expect any qualitative change of the results for the wurtzite-type InAs nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…For both contact configurations, see legend, the conductance exhibits an overall increase at increasing V g with reproducible mesoscopic fluctuations. Sizable conductance G ∼ 2e 2 /h around V g = 0 is a consequence of the Fermi level pinning at the surface of InAs, which results in surface charge accumulation in our nominally undoped NWs 13,14 . Roughly linear V g dependence of G is consistent with previous measurements on these and other similar NWs 19 .…”
mentioning
confidence: 99%
“…5. For bare InAs nanowires, it has been reported that the energy difference between near band-edge emission and surface-related emission is approximately ~ 35–45 meV [21]. However, for InGaAs nanowires, because the surface band bending is significantly reduced with increasing Ga composition, this energy difference would decrease simultaneously, and then electrons are less confined near the nanowire surface and holes are less localized at the nanowire center.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, for nanowires of some narrow-gap materials (such as InAs, In−rich InGaAs), the high density of surface states can lead to a bend of the electronic band structure near the nanowire surface (surface Fermi level pinned effect). Such a non-flat band structure will further cause charge carrier redistribution, which can strongly hinder the performance of optical nanowire-based devices [21]. Therefore, eliminating these surface states is highly necessary.…”
Section: Introductionmentioning
confidence: 99%